2006
DOI: 10.1016/j.adolescence.2005.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ thoughts about parents’ jobs and their importance for adolescents’ future orientation

Abstract: The current study examined the relation between adolescents’ perceptions of their parents’ jobs and their future orientation, and tested the role of parental support. Four hundred and fifteen ninth through twelfth graders were surveyed about their parents’ job rewards, self‐direction, and stressors, as well as their expectations for employment and education prospects. Results indicate that perceptions of parents’ rewards, self‐direction, and stress predict how positively or negatively adolescents perceive the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Workplace self-direction often characterizes professional more so than unskilled positions, but research with ethnic minority parents has found variability in levels of self-direction across low-wage jobs (Yoshikawa, 2011). Across varying work contexts, parents’ occupational self-direction has been positively associated with adolescents’ expectations for educational success (primarily African American families; Gardner Neblett & Schnabel Cortina, 2006) and mental health (fathers and pre-adolescent daughters, but not mothers, in dual-earner working-class families; Perry-Jenkins & Gillman, 2000), and protective against later problem behavior (for fathers of young children in nationally representative sample; Parcel & Menaghan, 1993). …”
Section: Parents’ Work Conditions and Adolescents’ Adjustmentmentioning
confidence: 99%
“…Workplace self-direction often characterizes professional more so than unskilled positions, but research with ethnic minority parents has found variability in levels of self-direction across low-wage jobs (Yoshikawa, 2011). Across varying work contexts, parents’ occupational self-direction has been positively associated with adolescents’ expectations for educational success (primarily African American families; Gardner Neblett & Schnabel Cortina, 2006) and mental health (fathers and pre-adolescent daughters, but not mothers, in dual-earner working-class families; Perry-Jenkins & Gillman, 2000), and protective against later problem behavior (for fathers of young children in nationally representative sample; Parcel & Menaghan, 1993). …”
Section: Parents’ Work Conditions and Adolescents’ Adjustmentmentioning
confidence: 99%
“…In addition, exploring the influence of gender and school grade seems necessary (Gould, Shaffer, Fisher, & Garfinkel, 1998;Neblett & Cortina, 2006;Sudak, Ford, & Rushford, 1984). Many studies have reported that interestingly, female students think more about suicide than male students (Sudak et al, 1984).…”
mentioning
confidence: 98%
“…The linkage found within the work domain fits with the ecological framework (Bronfenbrenner, 1986), showing that youth learn about adults’ work lives through their parents’ work experiences (Abramovitch & Johnson, 1992; Barling, Dupre, & Hepburn, 1998; Neblett & Cortina, 2006). The fairly weak associations suggest that parents’ experiences are not wholly transmitted to youth (Porfeli et al, 2013; Galinsky, 2010).…”
Section: Discussionmentioning
confidence: 53%
“…The implicit and explicit messages parents transmit about their experiences in the world of work constitute an influential source of information for their offspring. Some research indicates that youth have a reasonably accurate understanding of the general aspects of their parents’ work life, the hierarchical position of their parents’ jobs, their job satisfaction, and whether or not their parents are struggling with work (Abramovitch & Johnson, 1992; Barling, Dupre, & Hepburn, 1998; Neblett & Cortina, 2006; Piotrkowski & Stark, 1987). Youth learn about adults’ work lives through their parents’ experiences and this learning translates into youths’ motivation to work (Porfeli et al, 2008).…”
Section: Youths’ Socialization To School and Work In The Family Settingmentioning
confidence: 99%